An image of mitral valve repair. (November 2005) - Pritisanac, A; Schmidt, M; Hannekum, A; Gulbins, H
Mitral regurgitation is a severe problem of the mitral valve mechanism caused by many factors, including ischemic and nonischemic cardiomyopathy, inflammation, degeneration and others. Regardless of the cause of valve dysfunction, many changes in surgical approach have been undertaken. The pioneering work of Carpentier led to the era of mitral valve reconstruction a few decades ago. Understanding the different techniques applied in several pathoanatomic settings is of major interest. This review summarizes the indications and results of this specific surgical procedure in the setting of ventricular dysfunction by different causes.